2021
DOI: 10.1109/access.2021.3064503
|View full text |Cite
|
Sign up to set email alerts
|

Hermitian Rank Metric Codes and Duality

Abstract: In this paper we define and study rank metric codes endowed with a Hermitian form. We analyze the duality for F q 2-linear matrix codes in the ambient space (F q 2) n,m and for both F q 2-additive codes and F q 2m-linear codes in the ambient space F n q 2m. Similarly, as in the Euclidean case we establish a relationship between the duality of these families of codes. For this we introduce the concept of q mduality between bases of F q 2m over F q 2 and prove that a q m-self dual basis exists if and only if m i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…From the similar results established in [19] with respect to dual bases, and in [4] with respect to Hermitian inner product and q m -dual bases. Now for F Q m -linear rank metric code C ⊆ F n Q m and our given q sm -dual bases, we can obtain the result that λ B (C ⊥s ) = λ B (C) ⊥ M s as follows.…”
Section: Connections Between the S-galois Dual Of Rank Metric Codesmentioning
confidence: 55%
See 1 more Smart Citation
“…From the similar results established in [19] with respect to dual bases, and in [4] with respect to Hermitian inner product and q m -dual bases. Now for F Q m -linear rank metric code C ⊆ F n Q m and our given q sm -dual bases, we can obtain the result that λ B (C ⊥s ) = λ B (C) ⊥ M s as follows.…”
Section: Connections Between the S-galois Dual Of Rank Metric Codesmentioning
confidence: 55%
“…In recent years, the duality of rank metric codes has been extensively researched( [12], [14], [17], [19]). Cruz et al [4] defined the Hermitian form and introduced F q 2linear, F q 2 -additive and F q 2m -linear rank metric codes. The connections of duality with corresponding Hermitian inner products of those codes and the existence of q m -self-dual basis with respect to Hermitian form has been studied.…”
Section: Introductionmentioning
confidence: 99%
“…We choose interpolation-based decoding approach which is able to decode errors up to half of the minimum distance in polynomial time for all the aforementioned codes. A part of our work in this paper responds to a suggestion in [1], where the authors suggested studying the decoding of Hermitian rank metric codes.…”
Section: Introductionmentioning
confidence: 67%
“…A special class of maximum distance separable (MDS) codes, called Gabidulin codes was introduced in [13]. Detailed surveys of Gabidulin codes and their (Euclidean/Hermitian) duality can be found in [6], [7], [9], [19], [30]. Here, we investigate the e-Galois hull dimension of Gabidulin codes, in particular, by using a self-dual basis of F q m over F q , we H. Islam and A-L. Horlemann are with School of Computer Science, University of St. Gallen, Switzerland, (e-mail: habibul.islam@unisg.ch, annalena.horlemann@unisg.ch).…”
Section: Introductionmentioning
confidence: 99%